(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The article deals with the importance of English in global technology. technology continues to evolve and shape our world, the role of English will remain paramount, guiding us towards a future of greater connectivity, inclusiveness.